ڈاکٹرسراج الاسلام حنیف کی تحقیقاتِ حدیث : ایک تصنیفی جائزہ: Research Contributions of Dr. Sirāj-ul-Islam Ḥanīf in Ḥadīth (Al-Qamar, 2019)
Ḥadīth is the second primary and original source of Islamic Sharīʻah after Quran. Religious scholars from Khyber Pakhtunkhwa have remarkable contributions in the Ḥadīth sciences. Their works in different areas of the discipline comprise of different books, dūrūs and articles etc. This article gives an account of the contributions of an Islamic Scholar from Hussaī, Mardān, Dr. Sirāj-ul-Islam Hanīf in the relevant area. Dr. Hanīf has authored about sixty books in Arabic, Urdu & Pashto on Tafsīr, Fiqh and Ḥadīth, but his works focused the Ḥadīth sciences particularly Asmā al-Rijāl, Jarh wa Taʻdīl, Tahqīq, Ta’līq, Takhrīj etc.
Keywords: Ḥadīth; Khyber Pakhtūnkhwā; Sirāj-ul-Islam; Hanīf; Dar al-Quran Wa Sunnah